2004
DOI: 10.1021/ja038842w
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Transformation from Hydrophilicity to Hydrophobicity of Water Molecules on the Basis of Adsorption of Water in Graphitic Nanopores

Abstract: The interaction of water with hydrophobic surfaces is quite important in a variety of chemical and biochemical phenomena. The coexistence of water and oil can be realized by introduction of surfactants. In the case of water vapor adsorption on graphitic nanopores, plenty of water can be adsorbed in graphitic nanopores without surfactants, although the graphitic surface is not hydrophilic. Why are water molecules adsorbed in hydrophobic nanopores remarkably? This work can give an explicit insight to water adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
149
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 20 publications
8
149
1
1
Order By: Relevance
“…Another consequence of confinement effects is the formation of water clusters, which play a significant role in the stabilization of water in hydrophobic carbon micro and mesopores. [31,32] By forming clusters of 5 or more water molecules (cluster size of ∼ 1 nm), [31,[33][34][35]] the affinity of the water molecules can be transformed from hydrophillic to hydrophobic, [33] making their interaction with the CNT walls more favorable. While many previous studies have explored the mechanics, kinetics, and energetics of the entry of water molecules into uncapped single walled CNTs, [30,[36][37][38] the likelihood that a water molecule can enter the 3 inner region of a capped multiwalled CNT via wall defects is low (since the openings in the CNT walls are likely smaller than the cluster size), meaning that the exohedral physisorption of water is expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another consequence of confinement effects is the formation of water clusters, which play a significant role in the stabilization of water in hydrophobic carbon micro and mesopores. [31,32] By forming clusters of 5 or more water molecules (cluster size of ∼ 1 nm), [31,[33][34][35]] the affinity of the water molecules can be transformed from hydrophillic to hydrophobic, [33] making their interaction with the CNT walls more favorable. While many previous studies have explored the mechanics, kinetics, and energetics of the entry of water molecules into uncapped single walled CNTs, [30,[36][37][38] the likelihood that a water molecule can enter the 3 inner region of a capped multiwalled CNT via wall defects is low (since the openings in the CNT walls are likely smaller than the cluster size), meaning that the exohedral physisorption of water is expected.…”
mentioning
confidence: 99%
“…This is likely a result of the size and morphology of wall defects, which are smaller than the size of the water clusters (∼ 1 nm) that enable the physisorption of water onto the CNT walls. [31,[33][34][35] Recent work on graphite indicates that lattice monovacancies can become mobile at temperatures 200 • C, [59] and that the aggregation of these vacancies can lead to the formation of interlayer bonds, known as interlayer divacancies, [59][60][61] which can become the nucleation site for an extended interlayer defect, where two CNT wall planes become connected via a graphene ribbon.[60] The aggregation of native CNT wall defects likely do not provide continuous throughthickness pathways of sufficient size ( 0.6 nm) to enable the water clusters to enter the inner volume of the CNTs. Further work is necessary to determine the size and morphology of the native wall defects present in the CNTs used here, and the effect of the CNT structure and surface chemistry on the kinetics and energetics of the exohedral physisorption of water.…”
mentioning
confidence: 99%
“…Ohba et al clearly showed that cluster formation of water molecules is the reason why water molecules can adapt to hydrophobic pores. 48 Figure 9 shows total potential profiles for water molecular clusters in the slit-shaped hydrophobic pore. Here, only highly symmetric clusters were used for evaluation of the total interaction potential which is the sum of both molecule molecule and moleculewall interactions per a molecule.…”
Section: Accommodative Filling Of Water Molecules In Hydrophobic Spacesmentioning
confidence: 99%
“…As a result of these phenomena, dispersion interactions lose their superiority in adsorption of water in carbonaceous materials, in contrast to most organic and inorganic substances, where dispersion interactions play the main role [203]. Microporous carbon materials are known to have hydrophobic pore network structures [204][205][206] due to the non-polar nature of the graphitic carbon sheets inherent to their structure and the weaker carbon-water interactions compared to water-water interactions, which are dominated by electrostatic effects. This gives rise to an adverse adsorption isotherm at low loading, in which the level of electrostatically mediated hydrogen bonding is reduced.…”
Section: Water Adsorption and Transport In Microporous Carbonmentioning
confidence: 99%
“…Ohba et al have shown that larger water clusters have deeper potential depths inside the pore space [204], an indication of the adsorbed phase stabilization. Also, according to Kimura et al [205], the affinity change between water molecules and the pore wall may occur due to reduction of dipole moment of the water cluster, which gives rise to higher affinity of the water cluster towards the hydrophobic carbon wall at the level of pore filling.…”
Section: Water Adsorption and Transport In Microporous Carbonmentioning
confidence: 99%